Demonstrating a novel configuration of FPSE prototype working at medium temperature range - Ghozzi, Salem; Boukhanouf, Rabah (2016)
Numerous FPSE designs have been demonstrated, tested and maybe commercially produced for different applications since Beale had invented the first design of the FPSE. The proposed design of FPSE is intended to operate at atmosphere pressure and low heat source temperature for power generation applications. The proposed design aims to address some of the disadvantages associated to the FPSEs, such as seal leakage, hysteresis losses and side forces, with the considerations of the mechanism and assembly to be simple and straightforward. The focus was on the components and the design of the displacer and the power piston as they are of the main parts in the FPSE influence its operation and performance. The displacer and the power piston have improved by integrating sorts of flexible materials that being used in replace of the typical mechanical springs. The flexible metal component used in replace of the conventional mechanical springs has the properties of elasticity, rigidity, low density and low thermal conductivity beside its cylindrical housing shape. A prototype for the novel configuration with the integration of stainless bellows and rubber diaphragm is built to be work at low and medium temperature range. The engine is gradually improved so that the objectives of the configuration are achieved. The FPSE prototype is demonstrated and tested in the lab to assure that the new configuration is working properly. The engine is new in terms of design mechanical configuration; however, it showed aspiring results.